A Simple Flow-Cytometric Method Measuring B Cell Surface Immunoglobulin Avidity Enables Characterization of Affinity Maturation to Influenza A Virus - Gregory M. Frank (American Society for Microbiology, 2015)
ABSTRACT Antibody (Ab) affinity maturation enables an individual to maintain immunity to an increasing number of pathogens within the limits of a total Ig production threshold. A better understanding of this process is critical for designing vaccines that generate optimal Ab responses to pathogens. Our study describes a simple flow-cytometric method that enumerates virus-specific germinal center (GC) B cells as well as their AC50, a measure of Ab avidity, defined as the antigen concentration required to detect 50% of specific B cells. Using a model of mouse Ab responses to the influenza A virus hemagglutinin (IAV HA), we obtained data indicating that AC50 decreases with time postinfection in an affinity maturation-dependent process. As proof of principle of the utility of the method, our data clearly show that relative to intranasal IAV infection, intramuscular immunization against inactivated IAV in adjuvant results in a diminished GC HA B cell response, with increased AC50 correlating with an increased serum Ab off-rate. Enabling simultaneous interrogation of both GC HA B cell quantity and quality, this technique should facilitate study of affinity maturation and rational vaccine design. IMPORTANCE Though it was first described 50 years ago, little is known about how antibody affinity maturation contributes to immunity. This question is particularly relevant to developing more effective vaccines for influenza A virus (IAV) and other viruses that are difficult vaccine targets. Limitations in methods for characterizing antigen-specific B cells have impeded progress in characterizing the quality of immune responses to vaccine and natural immunogens. In this work, we describe a simple flow cytometry-based approach that measures both the number and affinity of IAV-binding germinal center B cells specific for the IAV HA, the major target of IAV-neutralizing antibodies. Using this method, we showed that the route and form of immunization significantly impacts the quality and quantity of B cell antibody responses. This method provides a relatively simple yet powerful tool for better understanding the contribution of affinity maturation to viral immunity.